2002
DOI: 10.1083/jcb.200202048
|View full text |Cite
|
Sign up to set email alerts
|

A twin arginine signal peptide and the pH gradient trigger reversible assembly of the thylakoid ΔpH/Tat translocase

Abstract: The thylakoid ΔpH-dependent/Tat pathway is a novel system with the remarkable ability to transport tightly folded precursor proteins using a transmembrane ΔpH as the sole energy source. Three known components of the transport machinery exist in two distinct subcomplexes. A cpTatC–Hcf106 complex serves as precursor receptor and a Tha4 complex is required after precursor recognition. Here we report that Tha4 assembles with cpTatC–Hcf106 during the translocation step. Interactions among components were examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
257
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(265 citation statements)
references
References 23 publications
5
257
0
3
Order By: Relevance
“…For example, they both possess a conserved glutamate residue in their predicted transmembrane domain, which theoretically should destabilize transmembrane helix insertion unless it is neutralized in some manner. Despite their structural similarities, Hcf106 and Tha4 seem to participate in different steps of the translocation process [8,9]. cpTatC is an integral membrane protein with six predicted membrane spanning helices and its amino and carboxyl termini exposed to the stroma [10,11].…”
mentioning
confidence: 99%
“…For example, they both possess a conserved glutamate residue in their predicted transmembrane domain, which theoretically should destabilize transmembrane helix insertion unless it is neutralized in some manner. Despite their structural similarities, Hcf106 and Tha4 seem to participate in different steps of the translocation process [8,9]. cpTatC is an integral membrane protein with six predicted membrane spanning helices and its amino and carboxyl termini exposed to the stroma [10,11].…”
mentioning
confidence: 99%
“…Following translocation, such translocons would disassemble, thus maintaining the permeability barrier. (6) In the peroxisome, 23 Pex proteins have been implicated in the translocation process, although for the most part, their functions remain unknown. Some information is available on those Pex proteins serving as target receptors for proteins bearing one of the two targetting signals employed by this system.…”
Section: Translocons For the Wholementioning
confidence: 99%
“…(4) In signalassembled translocons, folded proteins or higher-ordered complexes are delivered across the membrane at transiently formed sites in a manner that does not compromise the membrane permeability barrier. (5)(6)(7) Made for export The SecYEG complex in the bacterial plasma membrane and the homologous Sec61 complex in the ER membrane lie at the heart of classic examples of signal-gated translocons. In both of these protein export machines, microscopic, biochemical and biophysical studies have shown the translocon complexes to be arranged around a central cavity estimated to range between 9 and 60 Å , depending on the translocation status of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…Tat-targeted respiratory enzymes appear to have RR-leaders in only one subunit of the holoenzyme (8) that differs from general secretory pathway (Sec) signal peptides (82). Specifically, the RR-leader peptide is recognized at the membrane by a receptor complex formed from copies of TatB and TatC (80,81). It has been established by both in vivo and in vitro experiments that DmsD interacts with both TatB and TatC (34,51,52).…”
Section: Stages 9 To 11: Targeting To the Tat Transloconmentioning
confidence: 99%
“…The Tat translocon in E. coli is comprised of Tat A, B, and C subunits of which multiple copies of each are involved in the translocon (80,81). Tat-targeted respiratory enzymes appear to have RR-leaders in only one subunit of the holoenzyme (8) that differs from general secretory pathway (Sec) signal peptides (82).…”
Section: Stages 9 To 11: Targeting To the Tat Transloconmentioning
confidence: 99%